TEACHING ENGLISH TO YOUNG LEARNERS THROUGH TRADITIONAL GAMES - Rusiana, Rusiana; Nuraeningsih, Nuraeningsih (Language Circle: Journal of Language and Literature, 2016)
Teaching English for Elementary level is very important for preparing students to be ready and well prepared generation to be met with the future demand like communication and technology. In the light of communication, Indonesia is one of countries that join in agreement of ASEAN Economic Community which uses English as the language for global market in ASEAN. Dealing with communication, it is clear that nowadays almost all modern technology using English such as computer, gadget, etc. There are more student access internets or gadget for accessing game than playing the traditional ones. That is surely not a bad thing when students are exposed much to internet. Yet, being exposed to the traditional ones is also a good idea so that Indonesian students would be those who are aware of their own culture. Seeing those two things, the demand of being able to use English for communication and an effort of making the students aware of traditional games they have, we are interested in investigating the effectiveness of traditional games as a technique for teaching English for Elementary school students. Through games, teachers can create various contexts in which students have an opportunity to use English for communication, exchange information, and express opinion (Wright, Betteridge and Buckby, 1984). The aims of this resech is to find out whether traditional games are effective to be used in English teaching and learning. This research was conducted at SDIT Lukman al Hakim of fourth grader students with the number of students was 19. The design of the researh is quasi-experimental with one control group pre-test and post-test. The instruments are pre-test and post-test. The games which are used in this research are gedrik and betengan. The findings shows that traditional games are effective for teaching English. Suggestions are proposed for Englishngsinh teachers in implementing the technique in the class.